Instructional Supervision and Teacher Effectiveness in Senior Secondary Schools in Tambuwal Local Government Area, Sokoto State, Nigeria - Hiliya, Abbas Abubakar; Tambari, Umar; Sarkingobir, Yusuf; Hamza, Abdulrahman; Ashafa, Nafisa Abdulrahman (Universitas Terbuka, 2022)
Ã‚Â Education delves into issues in developing nations, including Sokoto; thus, poor supervision rendered public schools poor than private ones. The objective of the study was to investigate the relationship between instructional supervision and teacher effectiveness in senior secondary schools in Tambuwal local government area of Sokoto state, Nigeria using a correlational survey design. Therewith, 165 teachers and 9 principals were involved. Analysis shows that 84(52.5%) of teachers agreed that their planned lessons contain learner-centered activities, and 41(25.6%) strongly agreed. Teachers' responses on My principal ensures that I use teaching aids in teaching, 101(63.1%) agreed, 32(20%) strongly agreed, 12(7.5%), and 9(5.6%) disagreed and strongly disagreed, respectively. Regarding teachers' use of modern methods of teaching, 7(77.8%) of the principals agreed, and 2(22.2%) strongly agreed. Principals' responses on Teachers in my school ensure that students gain mastery of the content of instruction reveals 6(66.7%) of them agreed, 2(22.2%) were undecided, and 1(11.1%) strongly agreed. On teachers keeping records of vital information of instruction, most principals are positive as 4(44.4%) and 4(44.4%) agreed and strongly agreed, respectively; 1(11.1%) undecided. Principals submitted Teachers keeping records of studentÃ¢â‚¬â„¢s assessment 5(55.6%) as agreed, 3(33.3%) strongly agreed, and 1(11.1%) undecided. Pearson Product Moment Correlation shows a very high positive correlation between instructional supervision and the appropriateness of teaching methods used in the study area; likewise, there is a moderate positive relationship between instructional supervision and teacher record keeping. Effective supervision of secondary schools is needed for teacher effectiveness in schools in Tambuwal local government area and Sokoto state, Nigeria